Comparative study of different lithium salts as electrolyte additives of Li/SiOx–Si–C half-cells for lithium sulfur batteries - Deepa Elizabeth Mathew; R. Baby Dhanalakshmi; S. Sathya; M. Kathiresan; Sabu Thomas; Mohamed H. Alkordi; A. Manuel Stephan (SN Applied Sciences, 2023)
Abstract Silicon oxide and its derivatives (SiOx, 0 < x < 2) are drawing significant interest as electrode material for Li-ion and Li–S batteries owing to their unique properties of high specific capacity, low working potential, high abundance, and environmental friendliness. In-depth research is done on the effects of electrolyte additives on the electrochemical and interfacial characteristics of SiOx-based anodes for Li–S batteries. Two different electrolyte additives namely lithium bis (fluorosulfonyl imide) (LiFSI) and lithium bis (oxalatoborate) (LiBOB) were incorporated in the supporting electrolyte containing 1 M lithium bis (trifluoromethanesulfonyl imide) (LiTFSI) in tetraethylene glycol dimethyl ether (TEGDME): 1,3 dioxolane (DOL) in the ratio of 1:1 (v/v). The Li/SiOx–Si–C 2032-type half-cells were assembled, and their charge–discharge properties were explored at 0.1 C-rate. Surface morphology and electrochemical impedance investigations of the electrode materials have been performed after cycling. The interfacial properties of SiOx-based electrodes were examined by FTIR and XPS. Among the electrolytes studied LiFSI-added electrolytes offer superior charge–discharge properties, which was attributed to the formation of a stable solid electrolyte interphase (SEI) layer on the electrode surface. The surface chemistry studies revealed the formation of Li2CO3 and ROCO2Li peaks on the lithium metal surface. The formation of Li2CO3 and ROCO2Li compounds are identified on lithium surface by XPS data and complemented by NMR analysis.